2013
DOI: 10.1089/lrb.2012.0015
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Quality of Life and Patient Reported Outcomes in Patients with Oncologic Related Lower Extremity Lymphedema

Abstract: Background: Lower limb lymphedema (LLL) is a common complication of cancer treatment. The disease is chronic and progressive with no cure. Although a common and significant source of morbidity, the impact of this condition on health-related quality of life (HRQOL) has only recently been addressed. In effort to identify valid treatment strategies for LLL, we performed a systematic review, identifying studies describing HRQOL outcomes in patients with LLL secondary to cancer. Methods and Results: Seven medical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 20 publications
(45 reference statements)
0
37
0
4
Order By: Relevance
“…Cemal et al recently conducted a systematic review of studies investigating the HRQOL of patients with lymphedema of the lower extremity related to cancer treatment. 131 The authors identified only 6 studies that met the review's inclusion criteria, which included the use of a validated patient-reported outcome questionnaire. None of the studies were considered as level I evidence, and only one study used a patient-reported outcome instrument that was specific to cancer-related lymphedema.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%
“…Cemal et al recently conducted a systematic review of studies investigating the HRQOL of patients with lymphedema of the lower extremity related to cancer treatment. 131 The authors identified only 6 studies that met the review's inclusion criteria, which included the use of a validated patient-reported outcome questionnaire. None of the studies were considered as level I evidence, and only one study used a patient-reported outcome instrument that was specific to cancer-related lymphedema.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%
“…[1] It arises most commonly as a consequence of cancer or the treatments of cancer. Upper extremity lymphedema is commonly associated with the treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Secondary lymphedema is caused by various factors related to either lymphatic obstruction or lymphatic interruption due to inflammation, trauma, iatrogenic alterations of the lymph system (i.e., surgery or radiation), 3 or due to cancer therapy. 6,7,9,10 In developing countries, secondary lymphedema is predominantly caused by parasites, while in developed countries it most commonly occurs due to malignancies or malignancy-associated treatments. 2,3 Secondary lymphedema following cancer and related treatments is seen especially in patients with breast 11,12 and gynecological malignancies.…”
Section: Introductionmentioning
confidence: 99%